Physicochemical Characterization of Cullet to Glaze for Environmental Sustainability and Entrepreneurial Development - Ajadi, Michael; Lawal, Sulaimon; Babalola, Samson (International Journal of Environmental Sciences, 2023)
Purpose: Inability of ceramists to formulate glazes locally and the cost of importing glazes had resulted to the closure of many cottage ceramic industries in Nigeria. The study, physicochemical characterization of cullet to glaze, was conducted with the aim of recycling cullet for glazing earthen wares and the intention was to conduct elemental analysis of waste glass for glaze recipes, determine its artistic usage, lessen cullet from environment and harness the chemical properties for industrial development and economic growth. Methodology: Methodologies for the study involved laboratory analysis to determine oxides concentration in the cullet and studio artistic techniques to form glaze batches, batch-milling, glazes application on earthenware, and kiln firing. Four colours of windowpane cullet were used in order to determine their chromaticity effects as glaze. Cullet were pulverised with pulveriser machine (Rocklabs) and elemental analysis was carried out with tandem accelerator machine, using Particle Induce X-ray Emission to determine oxide compositions and concentrations. Findings: Elemental analysis revealed Na2O, MgO, K2O, Al2O3, SiO2, CaO, TiO2, PbO and FeO. SO3, P3O5, ZrO2, Rb2O, ZnO, MoO3, Sb2O5, SrO and BaO in varying concentrations as the oxides in the samples. The glass ceramic glazes gave good matt, glossy, opalescent, translucent and opaque results at 950oC kiln temperature. The reactions of additive fluxes on each formulated glaze batch with windowpane cullet assist hydrokinetics nature of their crystallisation phases in the kiln. Unique Contributions to Theory, Practice and Policy: The study is hinged on the circular economy theory; an approach towards designing out of waste and regenerating natural system. It explicates artists' ideas in recycling cullet for glaze derivation and highlights recycling benefits of cullet for environmental sustainability and entrepreneurial development. The study enhances the understanding of ceramists on how cullet can be utilized for glaze production and contributes to the development of practical strategies and solutions for stakeholders in ceramic field. The adaptation will ameliorate the problem of unavailability and high cost of glazes; stimulate rapid development of the Nigerian ceramic industry and heighten economic growth of Nigeria.